Development Of Hindu Character Values Education For Early Childhood - Sumertini, Ni Ketut; Sutresna, I Made (International Journal of Multidisciplinary Sciences, 2024)
In Hindu teachings, there is a wealth of universal character values that remain relevant to contemporary character education. Instilling Hindu character values should ideally begin in early childhood to lay a solid foundation for ethical and moral development. This study aims to analyze methods for developing Hindu character values in early childhood, focusing on three key principles: Tri Parartha, Tri Kaya Parisudha, and Tat Twam Asi. Using a library research method, data for this study was collected from journals, books, and other literature relevant to Hindu ethics and early childhood education. The research process involved setting objectives, gathering and selecting literature, reviewing content, analyzing data, synthesizing findings, and drawing conclusions. The results indicate that the development of Hindu character values in early childhood requires a multi-faceted approach that considers the unique developmental stages of children. Parental involvement is critical, serving as both facilitators and role models in imparting these values. Key methods include modeling ethical behavior in daily life (Tri Kaya Parisudha), fostering empathy and interconnectedness through the principle of Tat Twam Asi, and integrating communal values (Tri Parartha) into family and social interactions. Additionally, literacy activities and positive reinforcement play vital roles in embedding these teachings effectively. In conclusion, cultivating Hindu character values in early childhood not only nurtures ethical behavior but also aligns with the broader goals of character education. This approach emphasizes the importance of synergy between parents, educators, and cultural practices to ensure children internalize and live these values in their formative years.